2020
DOI: 10.1149/ma2020-01171mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of a CuF2/Cu Electrode for an All-Solid-State Fluoride Shuttle Battery

Abstract: Introduction The popularization of electrified vehicles connected to the smart grid community systems with stationary energy storage has attracted much attention as one of the solutions to global environmental problems. The critical technologies for such systems are rechargeable batteries with energy densities higher than that of conventional Li-ion batteries (LIBs). Among various candidates, all-solid-state fluoride-ion batteries (FIBs) operated by fluoride-ion transport [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Figure b shows the Arrhenius plot of the ionic conductivity of Pb 2 CuF 6 . The ionic conductivity of Pb 2 CuF 6 was 3.6 × 10 –8 S cm –1 at room temperature and 3.0 × 10 –5 S cm –1 at 140 °C; these values are much higher than those of CuF 2 (10 –11 S cm –1 at 140 °C) ,, and are comparable to those of β-PbF 2 at 23 °C (10 –8 to 10 –7 S cm –1 ). , The activation energy for the ionic conduction of Pb 2 CuF 6 was calculated to be 0.67 eV, which is almost the same as that of β-PbF 2 , indicating fluoride ion conduction through the [Pb 2 F 4 ] fluorite layer.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure b shows the Arrhenius plot of the ionic conductivity of Pb 2 CuF 6 . The ionic conductivity of Pb 2 CuF 6 was 3.6 × 10 –8 S cm –1 at room temperature and 3.0 × 10 –5 S cm –1 at 140 °C; these values are much higher than those of CuF 2 (10 –11 S cm –1 at 140 °C) ,, and are comparable to those of β-PbF 2 at 23 °C (10 –8 to 10 –7 S cm –1 ). , The activation energy for the ionic conduction of Pb 2 CuF 6 was calculated to be 0.67 eV, which is almost the same as that of β-PbF 2 , indicating fluoride ion conduction through the [Pb 2 F 4 ] fluorite layer.…”
Section: Resultsmentioning
confidence: 89%
“…Active materials such as BiF 3 ,, and CuF 2 ,, have high theoretical capacities because they can react with three and two fluoride ions per atom, respectively. In fact, Nakano et al demonstrated charge–discharge characteristics equivalent to the theoretical capacity using a 2.3 nm Cu thin film at 0.1 C. , However, CuF 2 has low electronic and ionic conductivities; thus, the theoretical capacity was not fully demonstrated in batteries composed of powders. The powdered CuF 2 operates at only approximately half the theoretical capacity, even at high temperatures and low rates. , …”
Section: Introductionmentioning
confidence: 99%